Perilaku Mental Accounting dalam Mengelola Daily Expenses dari Sisi Gaya Hidup Sehari-Hari Mahasiswa Indekos - Fika Yuliza; Fachruzzaman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Indekos students are an important segment of the academic community who need to support themselves financially. They usually live away from their parents' home and have to organise their own daily lives, including personal financial management. They often face various challenges in managing their finances to meet various needs such as boarding house rent, tuition fees, book fees, transportation costs, as well as non-academic expenses such as food and recreation costs. In this context, mental accounting behaviour is an interesting aspect to study because it can play an important role in the way boarding students manage their daily expenses. This study aims to find out how mental accounting behaviour plays a role in managing daily expenses and what are the factors that influence mental accounting in boarding students. Qualitative research with a phenomenological approach was chosen in this study to explore the phenomenon as a whole. After the research was conducted, it was found that mental accounting has a role in helping students manage their daily expenses. This can be seen from their behaviour of allocating money according to certain account categories such as boarding house rent, daily meals, skincare, transportation, academics and others.